2022
DOI: 10.18178/ijiet.2022.12.12.1762
|View full text |Cite
|
Sign up to set email alerts
|

Study of Project-Based Learning to Improve the Instructional Design Process of Pre-service Early Childhood Teachers

Abstract: The study aimed to identify the importance of training female early childhood teachers in educational design processes through project-based learning in order to improve their educational design processes. In addition, the study sought to identify the pros and cons of training on instructional design through project-based learning from the students' perceptions, and to provide recommendations and suggestions to overcome any negatives. A mixed-method research design was used in this study, in which a questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Duration of the study conducting the intervention or the time of pre-service teachers learning with the PjBL approach of the included articles varied quite widely, ranging from two weeks (Chung & Li, 2021) to a year (Kamali Arslantas & Kocaoz, 2021; Lee & Galindo, 2021), takes place in the years from 2019 to 2022. In which most of the included articles, this process takes place in about one-two semesters (no less than 16 weeks), including Al-Busaidi and Al-Seyabi (2021), Alromaih et al (2022), Brown and Jain (2020), Elfeky et al (2022), Habibi et al (2022), Hernández-Barco et al (2021, Huo et al (2021), Lin et al (2021), Martinez (2022), Poonpon (2021), Schina et al (2021), Tsybulsky and Muchnik-Rozanov (2023), Van Loi and Hang (2021), and Yustina et al (2020). The remaining studies had durations ranging from two to 15 weeks.…”
Section: Durationmentioning
confidence: 99%
See 2 more Smart Citations
“…Duration of the study conducting the intervention or the time of pre-service teachers learning with the PjBL approach of the included articles varied quite widely, ranging from two weeks (Chung & Li, 2021) to a year (Kamali Arslantas & Kocaoz, 2021; Lee & Galindo, 2021), takes place in the years from 2019 to 2022. In which most of the included articles, this process takes place in about one-two semesters (no less than 16 weeks), including Al-Busaidi and Al-Seyabi (2021), Alromaih et al (2022), Brown and Jain (2020), Elfeky et al (2022), Habibi et al (2022), Hernández-Barco et al (2021, Huo et al (2021), Lin et al (2021), Martinez (2022), Poonpon (2021), Schina et al (2021), Tsybulsky and Muchnik-Rozanov (2023), Van Loi and Hang (2021), and Yustina et al (2020). The remaining studies had durations ranging from two to 15 weeks.…”
Section: Durationmentioning
confidence: 99%
“…According to Aksela and Haatainen (2019) and Habibi et al (2022), teacher performance focusing on improving teaching quality can improve students' learning motivation and higher-order thinking abilities. For students, the main challenges are related to skills in using information technology to access information resources and implement projects (Aksela & Haatainen, 2019;Al Mulhim, 2022;Alromaih et al, 2022;Chung & Li, 2021), and authentic challenges such as the abilities to execute the research steps (Al-Busaidi & Al-Seyabi, 2021), focus on project participation (Alromaih et al, 2022), and the time management skills (Aksela & Haatainen, 2019;Kamali Arslantas & Kocaoz, 2021;Nava & Park, 2021). During the COVID-19 period, on the other hand, both teachers and students are under great pressure, and limited technology skills, inconvenient online communication, project time constraints, and inexperienced management skills have delayed their work (Poonpon, 2021;Prasetiyo et al, 2023), are also significant difficulties for the implementation of PjBL.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It also improved their collaborative learning, authentic learning, and iterative learning. Alromaih et al (2022) reported that using PBL to teach Saudi early childhood pre-service teachers about the instructional design process was very successful. Learning via PBL made ìthe design process valuable and impactful, not just theoretical information, and helped students to gain real experiences rather than memorized informationî (p. 1387).…”
Section: Pbl In Saudi Higher Education Contextmentioning
confidence: 99%